What do people bring into the game: experiments in the field about cooperation in the commons - Cárdenas, Juan-Camilo; Ostrom, Elinor (International Food Policy Research Institute, 2004)
The study of collective action requires an understanding of the individual incentives and of the institutional constraints that guide people in making choices about cooperating or defecting on the group facing the dilemma. The use of local ecosystems by groups of individuals is just one example where individual extraction increases well-being, but aggregate extraction decreases it. The use of economic experiments has enhanced the already diverse knowledge from theoretical and field sources of when and how groups can solve the problem through self-governing mechanisms. These studies have identified several factors that promote and limit collective action, associated with the nature of the production system that allows groups to benefit from a joint-access local ecosystem, and associated with the institutional incentives and constraints from both self-governed and externally imposed rules. In general, there is widespread agreement that cooperation can happen and be chosen by individuals as a rational strategy, beyond the “tragedy of the commons” prediction. A first step in this paper is to propose a set of layers of information that the individuals might be using to decide over their level of cooperation. The layers range from the material incentives that the specific production function imposes, to the dynamics of the game, to the composition of the group and the individual characteristics of the player. We next expand the experimental literature by analyzing data from a set of experiments conducted in the field with actual ecosystem users in three rural villages of Colombia using this framework. We find that repetition brings reciprocity motives into the decision making. Further, prior experience of the participants, their perception of external regulation, or the composition of the group in terms of their wealth and social position in the village, influence decisions to cooperate or defect in the experiment. The results suggest that understanding the multiple levels of the game, in terms of the incentives, the group and individual characteristics or the context, can help understand and therefore explore the potentials for solving the collective-action dilemma.